Dual antibiotics for bronchiectasis - Felix, Lambert M (Cochrane Database Syst Rev, 2018)
BACKGROUND: Bronchiectasis is a chronic respiratory disease characterised by abnormal and irreversible dilatation of the smaller airways and associated with a mortality rate greater than twice that of the general population. Antibiotics serve as front‐line therapy for managing bacterial load, but their use is weighed against the development of antibiotic resistance. Dual antibiotic therapy has the potential to suppress infection from multiple strains of bacteria, leading to more successful treatment of exacerbations, reduced symptoms, and improved quality of life. Further evidence is required on the efficacy of dual antibiotics in terms of management of exacerbations and extent of antibiotic resistance. OBJECTIVES: To evaluate the effects of dual antibiotics in the treatment of adults and children with bronchiectasis. SEARCH METHODS: We identified studies from the Cochrane Airways Group Specialised Register (CAGR), which includes the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Allied and Complementary Medicine (AMED), and PsycINFO, as well as studies obtained by handsearching of journals/abstracts. We also searched the following trial registries: US National Institutes of Health Ongoing Trials Register, ClinicalTrials.gov, and the World Health Organization (WHO) International Clinical Trials Registry Platform. We imposed no restriction on language of publication. We conducted our search in October 2017. SELECTION CRITERIA: We searched for randomised controlled trials comparing dual antibiotics versus a single antibiotic for short‐term (< 4 weeks) or long‐term management of bronchiectasis diagnosed in adults and/or children by bronchography, plain film chest radiography, or high‐resolution computed tomography. Primary outcomes included exacerbations, length of hospitalisation, and serious adverse events. Secondary outcomes were response rates, emergence of resistance to antibiotics, systemic markers of infection, sputum volume and purulence, measures of lung function, adverse events/effects, deaths, exercise capacity, and health‐related quality of life. We did not apply outcome measures as selection criteria. DATA COLLECTION AND ANALYSIS: Two review authors independently screened the titles and abstracts of 287 records, along with the full text of seven reports. Two studies met review inclusion criteria. Two review authors independently extracted outcome data and assessed risk of bias. We extracted data from only one study and conducted GRADE assessments for the following outcomes: successful treatment of exacerbation; response rates; and serious adverse events. MAIN RESULTS: Two randomised trials assessed the effectiveness of oral plus inhaled dual therapy versus oral monotherapy in a total of 118 adults with a mean age of 62.8 years. One multi‐centre trial compared inhaled tobramycin plus oral ciprofloxacin versus ciprofloxacin alone, and one single‐centre trial compared nebulised gentamicin plus systemic antibiotics versus a systemic antibiotic alone. Published papers did not report study funding sources. Effect estimates from one small study with 53 adults showed no evidence of treatment benefit with oral plus inhaled dual therapy for the following primary outcomes at the end of the study: successful management of exacerbation ‐ cure at day 42 (odds ratio (OR) 0.66, 95% confidence interval (CI) 0.22 to 2.01; 53 participants; one study; very low‐quality evidence); number of participants with Pseudomonas aeruginosa eradication at day 21 (OR 2.33, 95% CI 0.66 to 8.24; 53 participants; one study; very low‐quality evidence); and serious adverse events (OR 0.48, 95% CI 0.08 to 2.87; 53 participants; one study; very low‐quality evidence). Similarly, researchers provided no evidence of treatment benefit for the following secondary outcomes: clinical response rates ‐ relapse at day 42 (OR 0.57, 95% CI 0.12 to 2.69; 53 participants; one study; very low‐quality evidence); microbiological response rate at day 21 ‐ eradicated (OR 2.40, 95% CI 0.67 to 8.65; 53 participants; one study; very low‐quality evidence); and adverse events ‐ incidence of wheeze (OR 5.75, 95% CI 1.55 to 21.33). Data show no evidence of benefit in terms of sputum volume, lung function, or antibiotic resistance. Outcomes from a second small study with 65 adults, available only as an abstract, were not included in the quantitative data synthesis. The included studies did not report our other primary outcomes: duration; frequency; and time to next exacerbation; nor our secondary outcomes: systemic markers of infection; exercise capacity; and quality of life. We did not identify any trials that included children. AUTHORS' CONCLUSIONS: A small number of studies in adults have generated high‐quality evidence that is insufficient to inform robust conclusions, and studies in children have provided no evidence. We identified only one dual‐therapy combination of oral and inhaled antibiotics. Results from this single trial of 53 adults that we were able to include in the quantitative synthesis showed no evidence of treatment benefit with oral plus inhaled dual therapy in terms of successful treatment of exacerbations, serious adverse events, sputum volume, lung function, and antibiotic resistance. Further high‐quality research is required to determine the efficacy and safety of other combinations of dual antibiotics for both adults and children with bronchiectasis, particularly in terms of antibiotic resistance.